Analisis Pengaruh Penggunaan Sedimen Bendungan Bili Bili Sebagai Substitusi Agregat Halus Terhadap Kuat Tekan Beton - Chandra, Yoshua; Mursalim; Kalangi, Hendry Tanoto (Jurnal Media Teknik Sipil, 2025)
increase while the supply is getting smaller so that it needs a partial substitute alternative to concrete mixtures to overcome the limitations of using natural materials. The purpose of this study is to find out how much influence the compressive strength results from the substitution of fine aggregate with sediment from the Bili Bili Dam. The method used in this study is an experimental method that refers to the SNI 7656-2012 testing standard. The variation in the sediment percentage in this study was 0%, 2.5%, 5%, 7.5% and 10% of the weight of the fine aggregate used. The concrete quality planned in this study is 14.53MPa and uses cylindrical samples measuring Ø15cm and 30cm high, as well as cubes with a width of 15cm and a height of 15cm. Based on the results of the study, the compressive strength value for the use of sediment as a substitute for some fine aggregate successively reduced the compressive strength of concrete during the age of 3, 7, 14, 28 days from the planned concrete quality to be reduced by 3.8%, 13.67%, 22.10%, 34.44% and 48.72%, the cause of reduction by the high mud content in the sediment.